A five year follow-up of women with obstetric anal sphincter rupture at their first delivery. (August 2016) - Linneberg, Sidsel; Leenskjold, Stine; Glavind, Karin
Abstract: Objectives: Obstetric anal sphincter rupture (OASR) is considered a risk factor for subsequent fecal incontinence and suspected to be a risk factor for urinary incontinence and sexual dysfunction. The aims of this study were to assess risk factors for the different grades of OASR and to evaluate the clinical outcome five years after birth using validated questionnaires. Study design: A five year follow-up study was performed on 82 women with OASR during their first delivery in 2009. Case records were reviewed for known risk factors for OASR. Three questionnaires were mailed to the women: The St. Marks fecal incontinence score, The Danish anal sphincter rupture questionnaire (DASRQ) and a short supplemental questionnaire. The data were analyzed using Wilcoxon rank sum test, Fisher's exact test and Kruskal–Wallis test. Results: Fifty percent had an OASR 3a, 32% an OASR 3b, and 18% OASR 4. None of the investigated risk factors showed statistically significant difference according to the degree of rupture. Seventy-four percent of the women had some degree of fecal incontinence with a significantly higher frequency of fecal incontinence in rupture group 4 than in 3a. Forty-four percent had urinary incontinence and 50% had some sort of sexual dysfunction with no significant differences between the rupture groups. Conclusion: None of the investigated risk factors increased the incidence of more severe grades of rupture. Ninety-one percent of women with OASR at their first delivery had some degree of fecal or urinary incontinence or sexual dysfunction five years after. The symptoms of fecal incontinence showed a tendency to be more severe in women with more advanced sphincter rupture.